Promoting Independent Learning - Poghosyan, Ofelya; Ghumashyan, Varduhi (Armenian Folia Anglistika, 2015)
At present the role of independent learning has become more crucial than ever. The rapid development of close ties between the countries of the world, the requirement of urgent solutions to numerous problems connected with ecology, peace, politics, economy, art, etc. have strengthened the need for an international global language in order to exchange information between different cultures. Today this language is English and, consequently, learning English has become a must. The effectiveness of learning in general and that of independent learning in particular depends on the level of responsibility of the students. In other words, the student, who in fact is a learner, should have a clear idea of the plan of his/her study. The students should know how much time, effort and money they are going to ‘invest’ into their studies, and, moreover, they should be responsible for their own role in the interactive, student-centered ‘give and take’ process of learning a foreign language.